A Fiqh al-Muʿāmalāt Analysis of Islamic Contracts in Shopee E-Commerce Transactions: Reassessing the Role of the Salam Contract - Amin Nasrulloh; Sumarjoko Sumarjoko; Yusril Anwar; Eko Sariyekti (Yayasan Azhar Amanaa Yogyakarta, 2026)
The development of digital transactions through e-commerce platforms such as Shopee necessitates a fiqh al-mu‘āmalāt review of the relevance of classical contracts, particularly the salam contract and others. The salam contract, known as a sale in which payment is made in advance while the goods are delivered at a later time, aligns closely with the pattern of online transactions. This study aims to analyze the relevance of the salam contract in sales conducted on Shopee and to identify other contracts that are more appropriate to the characteristics of specific transaction features on the platform. The research adopts a qualitative approach through field studies, with data collected from interviews with fiqh al-mu‘āmalāt experts and transaction practitioners, supported by documentation and direct observation. Data validity was tested using source triangulation techniques. The findings indicate that most Shopee transactions involving advance payment followed by subsequent delivery fulfill the conditions and pillars of the salam contract. However, not all transactions can be categorized as salam. The Cash-on-Delivery (COD) feature is more akin to an ordinary sale, Shopee Food resembles a wakālah contract, PayLater tends toward a qarḍ contract, while pre-order transactions are more relevant to an istisnāʿ contract. Therefore, mapping contracts according to the characteristics of each transaction is essential to ensure that digital trade practices remain aligned with sharī‘ah principles.